Intensive Agriculture as Climate Change Adaptation? Economic and Environmental Tradeoffs in Securing Rural Livelihoods in Tanzanian River Basins - Ires, Idil (Frontiers in Environmental Science, 2021)
Tanzania is one of the East African countries most vulnerable to climate change impacts. Droughts and floods in 2015–16 had devastating effects on food production, crop failures and livestock deaths reaching record levels. One of the underlying projects of the Tanzanian government to mitigate these impacts is the Southern Agricultural Growth Corridors of Tanzania (SAGCOT), an area spanning the country’s largest river basin, the Rufiji, where it collaborates with national and transnational companies to intensify irrigated crop production. Irrigation, drought-tolerant seeds, and employment are three of the key government-advised strategies to help smallholders increase crop yield, adapt to climate change, and alleviate poverty through the corridor. However, little research is available on whether these goals have been achieved. This paper aims to contribute to the literature by assessing harvest and income levels following the 2015–16 drought. Through fieldwork conducted in 2016–17 in Usangu, a key paddy production area in the Great Ruaha Basin within SAGCOT, data is collected from documents and 114 informants. This study finds that irrigation did not significantly contribute to rising paddy production in the case study. Prioritizing the downstream national park and the energy sector, the government periodically cut down the water access of the case-study irrigation scheme, which exacerbated water stress. Moreover, though farmers widely shifted to intensive farming and used drought-tolerant seeds, mainly, the high-income groups ensured and increased the crop yield and profit. The-low income groups encountered crop failure and, due to rising production costs, debt. Many of them left farming, impoverished, and sought to secure subsistence through wage laboring. This study discusses the shortcomings of the transitions from traditional to intensive farming and from farming to employment as climate change adaptation strategies and draws critical policy-relevant conclusions.